Synthesis and antimicrobial evaluation of new 2-substituted 5,7-di-tert-butylbenzoxazoles - Vinsova, Jarmila; Cermakova, Katerina; Tomeckova, Alexandra; Ceckova, Martina; Jampilek, Josef; Cermak, Pavel; Kunes, Jiri; Dolezal, Martin; Staud, Frantisek (Bioorganic & medicinal chemistry, 2006)
Various synthetic pathways of the 30 novel 2-substituted 5,7-di-tert-butylbenzoxazoles as new potential antimicrobial drugs are discussed. The 28 intermediates are described as well. The compounds were characterized by 1H and 13C NMR spectra, MS spectra, IR/UV spectra and by means of CHN analysis. The purity of the final compounds was checked by HPLC and their lipophilicity (log K) was also determined by means of RP-HPLC. In the present study, the correlation between RP-HPLC retention parameter log K (the logarithm of capacity factor K) and various calculated log P data is shown. The target compounds were tested for their in vitro antimycobacterial activity. Several compounds showed antituberculotic activity comparable with or higher than the standard isoniazide. In vitro cytotoxicity testing of the most active benzoxazoles and isoniazide as a reference drug was performed using MTT assay and compared with isoniazide as a reference drug. Structure-activity relationships among the chemical structures, the physical properties and the biological activities of the evaluated compounds are discussed in the article.
Keywords: benzoxazoly; Mycobacterium tuberculosis; Models, Chemical; Benzoxazoles; Cell Line; Isoniazid; chemické modely; buněčné linie; Mycobacterium kansasii; vztahy mezi strukturou a aktivitou; isoniazid; mikrobiální testy citlivosti; Anti-Bacterial Agents; Humans; Microbial Sensitivity Tests; Structure-Activity Relationship; lidé; antibakteriální látky